Bioinspired Sandwich Structure in Composite Panels - Deepak Sampathkumar; Ashokkumar Mohankumar; Yuvaraja Teekaraman; Ramya Kuppusamy; Arun Radhakrishnan (Advances in Materials Science and Engineering, 2023)
The phenomenon of separation into constituent layers connecting the core and laminate of a composite sandwich complex is a vital complication that leads to early failure of such material. The direction of the sandwich construction's exfoliation rigidity is increased between interlaminar low fiber augmentation. The bioinspired technique of hybrid material layers was used on an aluminium face sheet with an interlayer composition of PET foam core and glass fabric of a material that appears to have greater potential as a flimsy substitute for materials currently used in automotive, aeronautical, and marine applications. This examination seeks to develop the making of such material along the retardation in fibre supplements. Fibre bridging has been recognized as an important appliance in the progress of this operating procedure. Consequently, this method points to promoting the event of fibre bridging by differing aggregates, including the mass and extent of augmented fibres and the quantity of epoxy resin applied. A few advancements were made to the production methods, and though the outcomes for the resisting ability of specimens were found to be indecisive, it was found that the layer separation hardness had even improved. This was confirmed through the operation of scanning electron microscopy and also predicted the mechanically peeled material surfaces which identified the adhesive strength variations with respect to the face sheet surface modified with the sand blasting process. The analysis also revealed the need for further research into optimizing the attachment between aluminium sheet and pet foam and glass fabric based hybrid sandwich panels.